2021
DOI: 10.1021/acs.joc.1c00467
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of β-l-Rhamnose Containing the Pentasaccharide Repeating Unit of the O-Specific Polysaccharide from a Halophilic Bacterium Halomonas ventosae RU5S2EL in the Form of Its 2-Aminoethyl Glycoside

Abstract: Total synthesis of the pentasaccharide repeating unit of the OPS from Halomonas ventosae RU5S2EL is accomplished through a [3+2] block strategy. Picoloyl-induced hydrogen-bond-assisted aglycon delivery (HAD) is used for two consecutive 1,2-cis-L-rhamnosylations, and remote participation is used for α-selective glucosylation. The choice of 2aminoethyl glycoside at the reducing end is opted for, leaving the scope for further glycoconjugate formation without hampering the reducing-end stereochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Glycosylation of disaccharide 25 with the glucoside donor 5 in the presence of NIS and TMSOTf at 0 °C gave the trisaccharide 26 in 80 % yield. The newly formed 1,2‐ trans [29] linkage of 26 was confirmed by the peaks at 4.84 ppm (d, 1H, J 1′′,2′′ 9.0 Hz, H‐1′) in the 1 H NMR and at 98.8 (C‐1′′) in the 13 C NMR. In a similar fashion, chloroacetate group was removed using thiourea and 2,4,6‐collidine [27] in CH 2 Cl 2 ‐MeOH=3 : 2 ( v/v ) to afford the corresponding 2‐OH derivative 27 in 75 % yield.…”
Section: Resultsmentioning
confidence: 83%
“…Glycosylation of disaccharide 25 with the glucoside donor 5 in the presence of NIS and TMSOTf at 0 °C gave the trisaccharide 26 in 80 % yield. The newly formed 1,2‐ trans [29] linkage of 26 was confirmed by the peaks at 4.84 ppm (d, 1H, J 1′′,2′′ 9.0 Hz, H‐1′) in the 1 H NMR and at 98.8 (C‐1′′) in the 13 C NMR. In a similar fashion, chloroacetate group was removed using thiourea and 2,4,6‐collidine [27] in CH 2 Cl 2 ‐MeOH=3 : 2 ( v/v ) to afford the corresponding 2‐OH derivative 27 in 75 % yield.…”
Section: Resultsmentioning
confidence: 83%
“…By following the general procedure, compound 1 (51.4 mg, 0.140 mmol) was converted to 6c (56 mg, 82%), which was obtained as a colorless oil: R f = 0.58 (25% EtOAc in hexanes); [α] D 20 −70.8 ( c 0.68, CHCl 3 ); 1 H NMR (500 MHz, CDCl 3 ) δ 7.38–7.29 (m, 7 H, ArH), 7.13–7.11 (m, 2 H, ArH), 5.52 (dd, J = 3.5, 1.5 Hz, 1 H, H-2), 5.36 (dd, J = 10.0, 3.5 Hz, 1 H, H-3), 5.29 (d, J = 1.5 Hz, 1 H, H-1), 4.72 and 4.69 (ABq, J AB = 11.5 Hz, 2 H, C H 2 Ar), 4.32 (dq, J = 9.5, 6.5 Hz, 1 H, H-5), 3.93 and 3.88 (ABq, J AB = 15.0 Hz, 2 H, C H 2 Cl), 3.60 (dd, J = 9.5, 9.5 Hz, 1 H, H-4), 2.32 (s, 3 H, C H 3 Ar), 2.12 (s, 3 H, COC H 3 ), 1.37 (d, J = 6.5 Hz, 3 H, H-6); 13 C­[ 1 H] NMR (126 MHz, CDCl 3 ) δ 170.1 ( C OCH 3 ), 166.2 ( C OCH 2 Cl), 138.2, 137.9, 132.7, 130.0, 129.5, 128.6, 128.0, 127.8 (Ar C ), 86.0 (C-1), 78.8 (C-4), 75.3 ( C H 2 Ar), 73.9 (C-3), 71.4 (C-2), 69.1 (C-5), 40.6 ( C H 2 Cl), 21.2 ( C H 3 Ar), 20.9 ( C OCH 3 ), 17.8 (C-6); IR (cast film) 3030, 2978, 2918, 1748, 1494, 1262 cm –1 ; HRMS (ESI-TOF) m / z : [M + Na] + Calcd for C 24 H 27 ClO 6 SNa 501.1109; Found 501.1107.…”
Section: Methodsmentioning
confidence: 99%
“…5 Recently, Perepelov et al reported the structure of the O-antigen from E. cloacae G3422 along with the gene cluster involved in the genesis of the said O-antigen. 6 In continuation of our efforts towards the chemical synthesis of bacterial oligosaccharides, 7–10 herein we report a convergent route towards the successful synthesis of the tetrasaccharide repeating unit of the O-antigen from E. cloacae G3422 in the form of its 2-aminoethyl glycoside ( 1 , Fig. 1).…”
Section: Introductionmentioning
confidence: 99%